Law of the wall in an unstably stratified turbulent channel flow. (17th September 2015) - Scagliarini, A.; Einarsson, H.; Gylfason, Á.; Toschi, F.
Abstract : We perform direct numerical simulations of an unstably stratified turbulent channel flow to address the effects of buoyancy on the boundary layer dynamics and mean field quantities. We systematically span a range of parameters in the space of friction Reynolds number ( Re_τ ) and Rayleigh number ( Ra ). Our focus is on deviations from the logarithmic law of the wall due to buoyant motion. The effects of convection in the relevant ranges are discussed, providing measurements of mean profiles of velocity, temperature and Reynolds stresses as well as of the friction coefficient. A phenomenological model is proposed and shown to capture the observed deviations of the velocity profile in the log-law region from the non-convective case.